Digitalisasi Kekayaan Intelektual Komunal di Indonesia: Digitalization of Communal Intellectual Property in Indonesia - Sulistianingsih, Dewi; Adhi, Yuli Prasetyo; Pujiono, Pujiono (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Intellectual property is one of the interesting issues to be discussed and continues to develop into a debate in the international world. The debate becomes stronger over communal intellectual property rights. In principle, intellectual property gets legal protection and becomes intellectual property rights. Intellectual property rights themselves consist of intellectual property rights that are personal and intellectual property rights that are communal. For Indonesia, which is rich in biodiversity and the nation's cultural wealth, which is very strong with the ownership of communal intellectual property rights. Individual intellectual property becomes a complete understanding for the Indonesian state, although at the beginning of its acceptance, personal intellectual property cannot be perfectly accepted by the Indonesian state. Currently, personal intellectual property has been able to be dynamic in the life of Indonesian people. The current debate is intellectual property rights that are communal. The Indonesian nation is rich in intellectual property rights, but why are there still obstacles in protecting communal intellectual property. This article is derived from research conducted using a normative juridical method with a statutory approach and a conceptual approach. The results of the study can be seen that the Indonesian government has made efforts to take an inventory of communal intellectual property in Indonesia. Digitization is the answer to the need for a communal intellectual property database in Indonesia.